SURVIVAL AND SEEDLING GROWTH OF MOON-EYED SNAIL (Turbo chrysostumus L.) ON DIFFERENT TEMPERATURE CONDITIONS - M. S. Hamzah (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2015)
Turbo chrysostumus is commonly known by fishermen community as moon-eyed snail and has common names of yellow-mouth turban or gold-mouth turban. These biota live in rocky beach and coral reefs surface filled with alga. They are also easily collected and used for high nutritive food for coastal villagers. The study of survival and growth of turbo youngsters in relation with different temperature is very limited. This study was done in January 5 – May 4, 2015 in the laboratory with the objective of observing the effect of optimum temperature range on their survival and growth. Based on ANOVA statistical analyses, the temperature had significsant effect on the survival of the turbo youngsters (p<0.05). “Honest Significant Difference” test revealed that control temperature (P1), 26±0.5°C (P2), and 28±0.5°C (P3) produced a significantly different effect on the survival compared with that in 30±0.5°C (P4). Higher growth rate was recorded in 26±0.5°C balanced with high food consumability. The relationship analysis of height shell-weight of wet body in all treatments indicated similar pattern of minor allometric (b<3). Keywords: survival, growth, moon-eyed snail (Turbo chrysostumus L.), temperature